The Effects of Dynamic Assessment on Reading Skill Performance: A Study of Indonesian EFL Learners - Andri Suherman (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2020)
This research article aimed to analyze the effects of Dynamic Assessment (DA) on EFL learners' reading comprehension. The participants in this case study were five Indonesian tertiary-level EFL learners. It investigated whether mediation in DA improve the learners reading comprehension performances and analyzed the extent to which mediation in DA benefit learning. The research methods used were pre-test, mediation, and post-test. The findings revealed two main points. First, the result of the post-test showed an overall improvement for all five students. As indicated by the effect size (0.96) and the result of paired samples t-test (p-value = 0.0028), it can be concluded that the effect of DA on the participants’ reading skill performance was highly significant. Second, mediation in DA appeared to benefit learning with different characteristics in each student. The implications of this study were to provide practical insight to EFL teachers into how mediation can be developed to improve learners' reading skills and to inform EFL teachers with some suggestions to carry out mediations to benefit learning.